2006
DOI: 10.1177/0149206305280115
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice in an Exchange Framework: Clarifying Organizational Justice Distinctions

Abstract: The authors used exchange theory to clarify distinctions between organizational justice types and considered the implications of recent conceptual developments regarding justice associated with interpersonal treatment (interactional justice) and the inclusion of justice associated with outcomes (distributive justice) for an exchange model of justice. Using two samples (401 part-time and 272 full-time employees), they found unique relationships of interactional justice and justice concerning informational adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 45 publications
5
155
0
4
Order By: Relevance
“…Employees take the quality of their organizational relationships into account when assessing justice in such a way JUSTICE AND TALENT MANAGEMENT OUTCOMES 23 that it increases their perceptions of procedural, interpersonal, and informational justice (Masterson, Lewis, Goldman, & Taylor, 2000;Piccolo, Bardes, Mayer, & Judge, 2008;Roch & Shanock, 2006). Relationships can be divided into two different categories: between employee and organization, or perceived organizational support (POS), and between employee and supervisor, or leader-member exchange (LMX) (Settoon, Bennett, & Liden, 1996).…”
Section: Role Of Social Exchange Relationships: Perceived Organizatiomentioning
confidence: 99%
“…Employees take the quality of their organizational relationships into account when assessing justice in such a way JUSTICE AND TALENT MANAGEMENT OUTCOMES 23 that it increases their perceptions of procedural, interpersonal, and informational justice (Masterson, Lewis, Goldman, & Taylor, 2000;Piccolo, Bardes, Mayer, & Judge, 2008;Roch & Shanock, 2006). Relationships can be divided into two different categories: between employee and organization, or perceived organizational support (POS), and between employee and supervisor, or leader-member exchange (LMX) (Settoon, Bennett, & Liden, 1996).…”
Section: Role Of Social Exchange Relationships: Perceived Organizatiomentioning
confidence: 99%
“…According to Simons and Roberson (2003), the perception of interactional justice can be understood as an element of procedural justice, which refers to policies, practices and procedures of the organization, whereas interactional justice refers to the way in which these factors are transmitted by the managers to the employees. The Social Exchange Theory, based on Blau (1964), has been used to understand the distinction between procedural and interactional justice (Masterson, Lewis, Goldman, & Taylor, 2000;Roch & Shanock, 2006 The perception of justice is related to aspects of assessment and judgment exercised in the organizational environment, which are present in the interaction between the individual and his job. Bakhshi et al (2009) found a significant correlation between organizational commitment and both procedural and distributive justice.…”
Section: Justice and Equity In Organizations: Complex Perceptionsmentioning
confidence: 99%
“…First, above mentioned researches has not used the four dimensions justice types separately in their analysis (Colquitt, Greenberg, & Zapata-Phelan, 2005;Roch & Shanock, 2006;Young, 2010). Using perceived organizational justice as a global measure in an investigation may not provide comprehensive understanding of underlying mechanism on the relationship between these variables with outcome variables such as OCBs.…”
Section: Conceptual Model Of Research and Hypothesesmentioning
confidence: 99%